2005
DOI: 10.1080/13554790590944636
|View full text |Cite
|
Sign up to set email alerts
|

Post Graphemic Impairments Of Writing: The Case Of Micrographia

Abstract: Micrographia (MG), an acquired impairment of writing characterized by diminution of letter size, coupled with slowing and loss of accuracy, is most frequently observed in the course of degenerative disease of basal ganglia, such as Parkinson's Disease. Only a few cases of MG without concomitant extrapyramidal signs have been described, mostly following vascular lesion of the left basal ganglia. In this article we report an isolated pattern of MG following an extensive traumatic cerebral lesion centered in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…In the lesion-based literature, peripheral processes have been most consistently associated with a left frontal–parietal network including, but not limited to, the dorsal premotor cortex and SPL (Exner, 1881; Ritaccio et al, 1992; Tohgi et al, 1995; Lubrano et al, 2004; Roux et al, 2009). In addition, peripheral dysgraphias have been described that are associated with damage to neural regions involved in general motor processing (not specifically in written language production) such as motor cortex, cerebellum, and various sub-cortical structures, e.g., caudate, putamen, and thalamus (Tanridag and Kirshner, 1985; Pramstaller and Marsden, 1996; Denes et al, 2005; Fournier Del Castillo et al, 2011). Finally, it is worth mentioning that spatial dysgraphias have been associated with some forms of spatial neglect (e.g., Caramazza and Hillis, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In the lesion-based literature, peripheral processes have been most consistently associated with a left frontal–parietal network including, but not limited to, the dorsal premotor cortex and SPL (Exner, 1881; Ritaccio et al, 1992; Tohgi et al, 1995; Lubrano et al, 2004; Roux et al, 2009). In addition, peripheral dysgraphias have been described that are associated with damage to neural regions involved in general motor processing (not specifically in written language production) such as motor cortex, cerebellum, and various sub-cortical structures, e.g., caudate, putamen, and thalamus (Tanridag and Kirshner, 1985; Pramstaller and Marsden, 1996; Denes et al, 2005; Fournier Del Castillo et al, 2011). Finally, it is worth mentioning that spatial dysgraphias have been associated with some forms of spatial neglect (e.g., Caramazza and Hillis, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…From the cognitive neuroscience perspective, the decrease in gamma band activity may be related to neural dysfunction in the frontal lobe 121 , reflecting impairment in the synchronous inhibition www.nature.com/scientificreports/ of pyramidal neurons 122 , and the GABAergic neurotransmission 123 . Furthermore, previous studies showed that the frontal lobe is involved in higher-order cognitive functions [124][125][126] . Concerning the frontal lobe dysfunction in paranormal beliefs 74 , the results of the present study also show that in paranormal believers as compared to skeptics, the absolute power of the beta was significantly reduced in the frontal area.…”
Section: Discussionmentioning
confidence: 99%
“…Bij een volgtaak moest men het verticale pad van een wit target op een zwart beeldscherm volgen met behulp van een hendel. De onderliggende oorzaak is niet duidelijk, maar een netwerk van de basale ganglia, thalamus en corticale gebieden speelt een cruciale rol bij het controleren van bewegingskracht, snelheid en amplitude bij onder andere het schrijven (Denes, Signorini & Volpato, 2005). Expliciete informatie blijkt voor gezonde personen een voordeel op te leveren bij het impliciet leren, wat te zien was aan afgenomen volgfouten en een verbeterde temporele voorspelling van het target.…”
Section: De Gevolgen Van Algemeen Letsel In De Basale Gangliaunclassified